The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1159/000016613
|View full text |Cite
|
Sign up to set email alerts
|

In situ Acid Resistance of in vivo Formed White Spot Lesions

Abstract: Thin sections of natural enamel lesions, so–called white spots (WS), and areas of sound enamel (SEn) adjacent to the WS were exposed to an intraoral environment for 2 weeks. Thin sections of WS samples, clamped in a PMMA holder, were microradiographed before and after exposure to intraoral conditions. Acid resistance was evaluated by lesion depth and mineral changes during the cariogenic challenge. The results show that there were statistically significant differences in lesion depth, mineral loss and mineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 22 publications
(32 reference statements)
1
21
0
5
Order By: Relevance
“…Finally, the interplay of erosion and abrasion on initial white spot lesions is not well understood, in particular with regard to in vivo situations where remineralization effects and the protective infl uence of the acquired pellicle or deposited salivary components should interfere with this complex pathology as has been indicated recently [Iijima and Takagi, 2000]. Therefore, further experiments are clearly warranted.…”
Section: Brushing Abrasion Of Initial Cariesmentioning
confidence: 99%
“…Finally, the interplay of erosion and abrasion on initial white spot lesions is not well understood, in particular with regard to in vivo situations where remineralization effects and the protective infl uence of the acquired pellicle or deposited salivary components should interfere with this complex pathology as has been indicated recently [Iijima and Takagi, 2000]. Therefore, further experiments are clearly warranted.…”
Section: Brushing Abrasion Of Initial Cariesmentioning
confidence: 99%
“…Thin sections (about 90 µm) including the WS lesions were prepared and exposed to oral conditions for 2 weeks continuously (Iijima and Takagi, 2000).…”
Section: Effect Of Time For Remineralizationmentioning
confidence: 99%
“…In vivo arrested lesions submitted to in vitro demineralization procedures presented higher acid resistance than sound enamel [Koulourides and Cameron, 1980]. An in situ demineralization study of in vivo arrested lesions showed similar results [Iijima and Takagi, 2000]. Arrested enamel lesions from extracted teeth are more resistant to intraoral cariogenic challenge than the adjacent sound tissue.…”
mentioning
confidence: 98%